Upacara Melasti Masyarakat Hindu dalam Acara Menyambut Peringatan Hari Nyepi di Pura Kahyangan Jagad Amerta Jati Pantai Balekambang Kabupaten Malang (Kajian Folklor) - Elsa Yulinda; Octo Dendy Andriyanto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The Melasti Ceremony is a significant purification ritual for the self and the universe performed by the Hindu community prior to Nyepi Day at Balekambang Beach, Malang Regency. This research aims to describe the origins, procedures, ceremonial equipment (ubarampe), societal perspectives, functions, and changes of the Melasti tradition through a folklore study. The research employs a descriptive qualitative method, with data collected through observation, documentation, and in-depth interviews with religious and community leaders. Findings reveal that the Melasti tradition at Balekambang has been practiced since the early 1980s, serving as a vital means of spiritual purification (bhuana alit and bhuana agung) and a forum for strengthening cultural identity. The ritual sequence, from Mendhak Toya Anyar to Larung Jolen, reflects the Hindu philosophy of harmony and gratitude. Despite technological adaptations and modifications in offering presentations, the sacred essence of the ritual remains preserved based on the Tri Hita Karana concept. This study implies that preserving local wisdom is essential for social solidarity and local economic development through religious tourism. It recommends sustainable preservation by actively involving the younger generation in cultural management.